Effect of plant extracts against Alternaria tenuissima (Kunze) Wiltshire in vitro - Shevchuk, O.; Golosna, L.; Afanasieva, O.; Zaslavskyi, O.; Pryvedeniuk, N.; Kutsyk, T. (Quarantine and plant protection, 2021)
Goal. To investigate the fungistatic effect of plant extracts on Alternaria tenuissima in vitro. Methods. The study was conducted in the Laboratory of Phytopathology of the Institute of Plant Protection of NAAS (IPP NAAS) and the Laboratory of Ecology and Pharmacognosy of Research Station of Medicinal Plants of the Institute of Agroecology and Environmental Management NAAS (RSMP IAEM NAAS). Medicinal plant raw materials used in the research were grown and selected at the research sites of DSLR IAP NAAS. Plant extracts were made on its basis. Determination of the activity of plant extracts on the growth of Alternaria tenuissima culture was performed in the laboratory of phytopathology of the IPP NAAS. Agar-disk diffusion method was used. The radial growth rate and the percentage of growth inhibition of colonies were determined. Results. On the 5th day after the start of the experiment, all studied extracts formed colonies of significantly smaller size compared to the control. On the 7th day, extracts of sage, thyme, annual wormwood, wormwood, echinacea root, and plume poppy significantly inhibited the development of Alternaria tenuissima colonies. On the 10th day, a significant reduction in the growth of colonies of the pathogen occurred with the use of extracts of sage, annual wormwood, echinacea roots and plume poppy. Inhibition of colony growth was highest for sage, annual wormwood and plume poppy and ranged from 84.3—99.5% on day 5 to 38.1—73.4% on day 10 after inoculation. Conclusions. According to our results, extracts of sage (Salvia officinalis L.), annual wormwood (Artemisia annua L.) and plume poppy (Macleaya cordata L.) showed a pronounced fungistatic effect against Alternaria tenuissima. These data suggest that extracts of these plants can be used in the future to develop plant protection products.